Methods in detection of median filtering in digital images: a survey - Ahmed, Sajjad; Islam, Saiful (Multimedia tools and applications, 2023)
When it comes to reducing impulsive noise from digital photos, the Median Filter (MF) is a nonlinear filter that can be employed effectively. This nonlinear filter is used to erase traces left by other linear filters due to the fact that they are nonlinear in nature. The application of a median filter on an image raises questions about the image’s genuineness when it is discovered. For the detection of median filtering, a slew of approaches has been developed. The main purpose of this paper is to explain different parts of median filter forensics, look at some new and existing techniques in median filter forensics, and compare the pros and cons of each technique. We also developed a taxonomy to broadly classify various methods proposed for median filter forensics. In addition, we also discussed and describe the popular testing procedure that researchers in the field are using to evaluate the median filtering detection methods and may be employed as a testing framework for future studies, for other operator detection as well as for general purpose image forensics.